Studi Analisis Tentang Anak Hiperaktif Dan Upaya Mengatasinya Pada Siswa Kelas III SD Muhammadiyah 5 SurakartaTahun Ajaran 2015/2016 - Rahayu, Putri Pangesti (2016)
Faculty of Teacher Training and Education, Muhammadiyah University Surakarta February, 2016. Based on the results of observations by researchers in SD Muhammadiyah 5 Surakarta, these results indicate that there are two students who have hyperactivity in class III, and there are some teachers handling for hyperactive children. This study aimed to describe: ( 1 ) the behavior of hyperactive children in class III SD Muhammadiyah 5 Surakarta, ( 2 ) factors that cause child hyperactivity in class III SD Muhammadiyah 5 Surakarta, ( 3 ) countermeasures for hyperactive children in class III SD 5 Muhammadiyah Surakarta. This research is qualitative. Subjects in this study were principals, teachers who teach in class III, hyperactive children in class III, and parents. Data collection techniques used are observation, interview, documentation, and field notes. The analysis technique used is descriptive qualitative with interactive analysis consists of three components of the analysis, namely data reduction, data presentation, and conclusion. This study begins with a preparation phase, the implementation of research, preparation of reports and end with reporting. The results showed that the Radit's behavior as hyperactive children, among others: often interfere with another friend, do not want to be regulated, often leaves seat when learning, and often do not complete the task that has been done. Meanwhile, Leo's behavior as hyperactive children, among others: has a high temperament, often hurt others, often leaves seat when learning, and spoiled. These behaviors are caused by environmental factors or a family home. through interviews with the parents of the child that the parents Radit often provide physical violence or words when guiding children, while parents often indulge Leo and to the wishes of the child. The behavior of hyperactive children caused by these factors can be overcome with some effort, among others: given a warning when they made mistakes, provide appropriate sanctions ability of children, do not have to provide when guiding a hyperactive child abuse. So every hyperactive child that has a different behavior, a factor which is also different and efforts to overcome them is different according to the level kehiperaktifannya. Keywords:hiperakttif children, overcome